A theory that predicts behaviors of disordered cytoskeletal networks. Issue 9 (27th September 2017) - Belmonte, Julio M; Leptin, Maria; Nédélec, François
Abstract: Morphogenesis in animal tissues is largely driven by actomyosin networks, through tensions generated by an active contractile process. Although the network components and their properties are known, and networks can be reconstituted in vitro, the requirements for contractility are still poorly understood. Here, we describe a theory that predicts whether an isotropic network will contract, expand, or conserve its dimensions. This analytical theory correctly predicts the behavior of simulated networks, consisting of filaments with varying combinations of connectors, and reveals conditions under which networks of rigid filaments are either contractile or expansile. Our results suggest that pulsatility is an intrinsic behavior of contractile networks if the filaments are not stable but turn over. The theory offers a unifying framework to think about mechanisms of contractions or expansion. It provides the foundation for studying a broad range of processes involving cytoskeletal networks and a basis for designing synthetic networks. Synopsis: The contraction or expansion rates of disordered cytoskeletal networks is predicted based on the properties of the filaments, and the molecular motors and crosslinkers that link them. The prediction is calculated analytically for networks made of flexible, semi‐flexible (actin) and rigid (microtubule) filaments. It explains the combined contribution of crosslinkers and motors in producing contraction of actomyosin systems. The theory reveals new conditions to produce contractile or expansile cytoskeletal networks. It unifies previously proposed mechanisms of contraction into a common framework. Abstract : The contraction or expansion rates of disordered cytoskeletal networks is predicted based on the properties of the filaments, and the molecular motors and crosslinkers that link them.